Specific inhibition of ectodomain shedding of glycoprotein lba by targeting its juxtamembrane shedding cleavage site - Liang, X; Russell, S; Estelle, S; Jones, L; Cho, S; Khan, M; Berndt, Michael; Bunting, S; Ware, J; Li, R (Thieme Medical Publ Inc, 2013)
Background: Ectodomain shedding of glycoprotein Ibα (GPIbα), a proteolytic event in which metalloprotease ADAM17 cleaves the Gly464-Val465 bond and releases glycocalicin to the plasma, is considered a critical step in mediating clearance of stored platelets. Supporting evidence has largely come from studies using ADAM17 inhibitors. However, the definitive proof is lacking due to the broad substrate specificity of ADAM17. Aim: To achieve substrate-specific inhibition of GPIbα shedding. Methods: Development of monoclonal antibodies that directly bind the sequence around the GPIbα shedding cleavage site and inhibit GPIbα shedding by blocking ADAM17 access to the cleavage site. Results: Six anti-GPIbα monoclonal antibodies with varying binding affinities were obtained. The prototypic clone, designated 5G6, and its monomeric Fab fragment bind specifically purified GPIb-IX complex, human platelets, and transgenic murine platelets expressing human GPIbα. The clone 5G6 showed similar inhibitory potency as a widely used shedding inhibitor GM6001 in both constitutive and induced GPIbα shedding in human platelets. It does not recognize mouse GPIbα or inhibit shedding of other platelet receptors. Finally, 5G6 binding displays no detectable effect on platelet activation and aggregation. Conclusions: The clone 5G6 specifically inhibits GPIbα shedding with no detectable effect on platelet functions. The method of substrate-specific shedding inhibition by macromolecular binding of the shedding cleavage site can be applicable to many other transmembrane receptors undergoing ectodomain shedding.